Chinese Pure Online-Channel Retailers Implement the Strategy Transformation to Omni-Channel Retailing - Sun, shuhan (2018)
As an emerging market strategy in the retail sector, omni-channel retailing aims to coordinate processes and technologies across supply and sales channels. In academia, the concepts of omni-channel retailing are still nascent, and the number of academic literature on this subject is very limited. This dissertation aims to explore the concept of omni-channel and its implement in relevant firm operating in the Chinese market. Lots of retailers have become the player to develop multichannel and omnichannel strategies by adding touchpoints to interact with their customers. Therefore, a managerial perspective is vital for gathering insights into the retailer’s current strategy and the challenges they face when configuring omni-channel integration. This research employs an interpretive-based approach and takes the form of an exploratory a case study through the in-depth investigation of the relevant retailer. Qualitative data was collected from the semi-interviews. The conclusion of this dissertation is that the investigated retailer still has a long way to go in their integrative efforts. Since there are some undeveloped channel strategies in their omni-channel implementation. While it can be said that the investigated retailer channel integration degree is far ahead in the Chinese market. Additionally, through empirical research, the final survey results show that although the omni-channel concept in the literature needs to be modified, it is also basically applicable to China's developing market context.